LEGAL GUARANTEES FOR THE IMPLEMENTATION OF THE RULE OF LAW IN ADMINISTRATIVE DELICTOLOGY - Borodin, Ivan; Lazarev, Anatoliy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: the aim of this article is to analyze the guarantees for the implementation of the rule of law in administrative delictology, which is relevant in the modern stage of the development of the rule of law, a social state, and a democratic society. When forming a democratic society, it is essential to remember that democracy is a political regime based on popular sovereignty. In the process of implementing constitutional rights and freedoms of individuals, maintaining public order and public safety in administrative delictology, the principles of the rule of law and its guarantees are fundamental. Methods: phenomenological; comparative legal; sociological; logical; dialectical. Results: the proposed criteria for classifying guarantees of the rule of law as a legal phenomenon should serve the development of scientific thought within the specified paradigm and become, to a certain extent, the basis for further elaboration and improvement of administrative and legal norms that shape the procedures for conducting cases of administrative offenses. The discussion of the issues related to the system of guarantees of the rule of law in the process of handling cases of administrative offenses should be carried out in the context of new perspectives that drive changes in the administrative delict process in Ukraine. By guarantees of the principle of the rule of law in administrative delictology, we should understand objective and subjective conditions, organizational measures, as well as specific legal instruments that need to be established by the legislator. To ensure the guarantees for the implementation of the principle of the rule of law in administrative delictology do not remain mere theoretical constructs, they must genuinely represent the necessary means of organizational and legal nature on behalf of the state and society. Only by ensuring proper guarantees, the principle of the rule of law represents a social value, both for society as a whole and for individual citizens, as it forms the basis of existence in the legal space, including legal culture and traditions. By guarantees of the principle of the rule of law in administrative delictology, we should understand objective and subjective organizational measures, as well as special legal instruments that need to be established by the legislator. In order for the guarantees for the implementation of the principle of the rule of law in administrative delictology not to remain mere theoretical constructs but to genuinely represent necessary means of organizational and legal nature on behalf of the state and society, it is important for them to have an absolutely objective character.